Calcined low-grade multimineral clays as supplementary cementitious materials: a feasibility study. Issue 3 (3rd May 2020) - Rakhimova, Nailia R.; Rakhimov, Ravil Z.; Bikmukhametov, Artur R.; Morozov, Vladimir P.; Eskin, Aleksey A.; Gubaidullina, Alfiya M.
ABSTRACT: The relevance of calcined clays as sources with great potential for low-clinker blended Portland cements has significantly increased in recent decades. This article reports on a study to evaluate the potential of the two low-grade clays containing 9.37% of montmorillonite/chlorite and 12.26% of montmorillonite/kaolinite/chlorite accompanied with 29.73% and 32.79% of calcite, respectively, as supplementary cementitious materials. The clays after thermal treatment at 800°C demonstrated poor pozzolanic activity, slight increase in the C-(S)-H and decline in the CH contents, and decrease in the mechanical properties of the blended Portland cement pastes. The results showed that the investigated clays fall below the range of the clays suitable for pozzolan production.